Penatalaksanaan Perawatan Saluran Akar pada Fraktur Gigi 21 disertai Perforasi - Zieta Sakinah Emdi; Reni Nofika (Faculty of Dentistry Universitas Andalas, 2019)
Root canal treatment aims to maintain the condition of the teeth in order to keep them functioning. In practice, the treatment procedure does not always run smoothly, the operator can face undesirable conditions that can affect the prognosis of treatment. A common procedural error during root canal treatment is a lateral root perforation which must be treated immediately to avoid further damage. The success of the perforation treatment is determined by the materials used. One of the bicompatible materials to seal lateral perforations using MTA (mineral trioxide aggregate). Successful root canal treatment affects treatment outcomes, so proper restoration is required to reduce the risk of marginal leakage. The choice of final restoration in post-root canal treatment depends on the amount of remaining tooth structure, horizontal pressure and chewing load. For post-root canal treatment anterior teeth with intact marginal edges, direct restoration can be performed using composite resin